Mixing Eucalyptus and Acacia trees leads to fine root over-yielding and vertical segregation between species - Laclau, Jean-Paul [UNESP]; Nouvellon, Yann; Reine, Caroline; Gonçalves, José Leonardo de Moraes; Krushe, Alex Vladimir; Jourdan, Christophe; le Maire, Guerric; Bouillet, Jean-Pierre (Springer Nature, 2013)
The consequences of diversity on belowground processes are still poorly known in tropical forests. The distributions of very fine roots (diameter <1 mm) and fine roots (diameter <3 mm) were studied in a randomized block design close to the harvest age of fast-growing plantations. A replacement series was set up in Brazil with mono-specific Eucalyptus grandis (100E) and Acacia mangium (100A) stands and a mixture with the same stocking density and 50 % of each species (50A:50E). The total fine root (FR) biomass down to a depth of 2 m was about 27 % higher in 50A:50E than in 100A and 100E. Fine root over-yielding in 50A:50E resulted from a 72 % rise in E. grandis fine root biomass per tree relative to 100E, whereas A. mangium FR biomass per tree was 17 % lower than in 100A. Mixing A. mangium with E. grandis trees led to a drop in A. mangium FR biomass in the upper 50 cm of soil relative to 100A, partially balanced by a rise in deep soil layers. Our results highlight similarities in the effects of directional resources on leaf and FR distributions in the mixture, with A. mangium leaves below the E. grandis canopy and a low density of A. mangium fine roots in the resource-rich soil layers relative to monospecific stands. The vertical segregation of resource-absorbing organs did not lead to niche complementarity expected to increase the total biomass production. © 2012 Springer-Verlag Berlin Heidelberg.
Keywords: Acacia; Biomass; Competition; Diversity; Eucalyptus; Facilitation; Forest; Niche; Productivity; biological production; biomass allocation; evergreen tree; facilitation; fine root; forestry production; legume; phytomass; plantation forestry; species diversity; stand structure; tropical forest; Brazil; Acacia mangium; Eucalyptus grandis